Self-organization of a biogeomorphic landscape controlled by plant life-history traits - Schwarz, Christian; Gourgue, Olivier; Jim van Belzen; Zhu, Zhenchang; Bouma, Tjeerd J; van de Koppel, Johan; Ruessink, Gerben; Nicolas, Claude; Temmerman, Stijn (Nature geoscience, 2018)
Feedbacks between geomorphology and plants are increasingly recognized as key drivers shaping a variety of landscapes. Most studies of biogeomorphic interactions have focused on the influence of physical plant characteristics, such as stem and root density, on landscape morphodynamics without considering the role of life-history traits. However, pioneer plants can have very different colonization behaviours. Fast colonizers are characterized by a high number of establishing seedlings that produce homogenous vegetation patterns. In contrast, slow colonizers are characterized by a low number of establishing seedlings that are able to expand laterally, resulting in patchy vegetation patterns. Here we combine biogeomorphic model simulations and field observations in the Western Scheldt Estuary, the Netherlands, to show that colonization behaviour can influence the evolution of wetland landscapes. We find that colonization by fast colonizers favours stabilization of pre-existing channels and consolidation of the landscape configuration. In contrast, colonization by slow colonizers facilitates the formation of new channels and thereby actively facilitates further landscape self-organization. Our findings underline the key role of life-history traits in steering landscape self-organization across different biogeomorphic systems, and potentially the long-term resilience of these landscapes to disturbances.